Insights into the charge carrier dynamics in perovskite/Si tandem solar cells using transient photocurrent spectroscopy - Ghorai, A; Kumar, P; Mahesh, S; Lin, Y-H; Snaith, HJ; Narayan, KS (AIP Publishing, 2022)
Direct bandgap perovskite and indirect bandgap Si, which form the two active layers in a tandem solar cell configuration, have different optoelectronic properties and thicknesses. The charge-carrier dynamics of the two-terminal perovskite-on-Si tandem solar cell in response to a supercontinuum light pulse is studied using transient photocurrent (TPC) measurements. Spectral dependence of TPC lifetime is observed and can be classified into two distinct timescales based on their respective carrier generation regions. The faster timescale (∼500 ns) corresponding to the spectral window (300-750 nm) represents the top-perovskite sub-cell, while the slower timescale regime of ∼25 μs corresponds to the bottom-Si sub-cell (>700 nm). Additionally, under light-bias conditions, the transient carrier dynamics of the perovskite sub-cell is observed to be coupled with that of the Si sub-cell. A sharp crossover from the fast-response to a slow-response of the device as a function of the light-bias intensity is observed. These results along with a model based on transfer matrix formulation highlight the role of charge-carrier dynamics in accessing higher efficiencies in tandem solar cells. The carrier transit times and lifetimes in addition to their optical properties need to be taken into account for optimizing the performance.